Real‐world assessment of topical glaucoma medication persistence rates based on national pharmaceutical claim data in a defined population. (16th May 2019) - Zhu, Zhuoting; Jiang, Yu; Wang, Wei; Scheetz, Jane; Shang, Xianwen; Zhang, Lei; He, Mingguang
Abstract: Importance: The rate and determinants of persistence to topical glaucoma medications are important for identifying patients at high risk of discontinuing medications and designing targeted approaches to improve persistence. Background: To evaluate the rate and determinants of persistence to topical glaucoma medications among middle‐aged and older Australian adults. Design: Population‐based cohort study. Participants: Participants in need of persistent topical glaucoma medications in the 45 and Up Study. Methods: The 45 and Up Study is a large‐scale population‐based cohort study. Participants were classified as needing persistent topical glaucoma medications if at least three claims with related prescriptions were recorded. Persistence was defined as topical glaucoma medications were filled within 90 days. Main Outcome Measures: The rates and determinants of medication persistence at 2‐year follow‐up. Results: A total of 12 899 patients requiring persistent topical glaucoma medications were identified. Among them, 9019 (69.9%) had persisted with their glaucoma medications for at least 2 years. Multiple logistic regression analysis documented significant effects of patient‐related factors (gender, socioeconomic status, language spoken at home, lifestyle and comorbidities) and drug‐related factors (total number and drug class) on the persistence rate. Those most at risk groups of non‐persistence were those patients living in remote areas (odds ratio, OR: 0.59, 95% confidence interval, CI: 0.37‐0.92), having family income over 70 000 AUD/year (OR: 0.53, 95% CI: 0.45‐0.62), speaking other languages at home (OR: 0.61, 95% CI: 0.53‐0.68), and using cholinergic classes of medications (OR: 0.55, 95% CI: 0.38‐0.79). Conclusions and Relevance: Our data has shown a medium level of persistence to topical glaucoma medication among middle‐aged and older Australian adults. However, efforts are still needed to improve the rate of persistence.